THE INFLUENCE OF INTELLECTUAL CAPITAL AND SHARIA COMPLIANCE IMPLEMENTATION OF LOCAL GOVERNMENT REGULATION OF NO SMOKING AREA IN GOVERNMENT INSTITUTIONS (PERDA KTR) IN BLITAR CITY - Denny Arinanda Kurnia; Farkhan Evendi (Universitas Islam Balitar, 2020)
This research is use to find out about the implementation of the Local Government Regulation on KTR (No Smoking Area) in the government agency of Blitar City. The focus of this paper is on policy in the application of Local Government Regulations related to KTR in Blitar City. The established KTR policy aims to harmonize the rights of smokers and the right of health with healthy living behaviors. Data collection methods are in-depth interviews, in addition to the community, also with several government agencies in Blitar City that have been chosen such as the Blitar City Government and the Public Health Office. In conclusion, the KTR Local Government Regulation in addition to being a form of implementing the law, is also a point of harmonization between the rights of smokers and non-smokers to breathe clean air.